Protokol New Normal Order Pasca Pandemi COVID-19 dalam Pengembangan Kampoeng Boenga Grangsil Berbasis Masyarakat - Respati Wikantiyoso; Diyah Sukanti Cahyaningsih; Aditya Galih Sulaksono; Sri Widayati (University of Merdeka Malang, 2020)
The tourism development sector in Indonesia is overgrowing. During the COVID-19 pandemic, it was the sector most affected economically. The COVID1-9 pandemic has changed the